Creative Communication: Implementing Sign Language Learning through Interactive Videos to Develop Inclusive Education in Early Childhood Education in Medan Tuntungan District - Putri Sari Ulfa Sembiring; Roy Nuary Singarimbun (Outline Journal of Education, 2025)
This study aims to develop a model of creative communication through the implementation of sign language learning using interactive videos as an effort to support inclusive education in Early Childhood Education (ECE) in Medan Tuntungan District. In an inclusive educational environment, children with special needs require adaptive and communicative learning approaches in order to interact effectively. Interactive videos are considered an engaging and effective medium for introducing sign language to children, teachers, and their peers. This research employs a descriptive qualitative approach, with data collected through observations, interviews, and documentation. The results show that the use of interactive videos in sign language learning can enhance participation, communication understanding, and inclusivity in classroom learning activities. This implementation also strengthens the awareness of teachers and students about the importance of embracing diversity and creating a learning environment that is welcoming for all children.